2022
DOI: 10.3389/fpsyg.2022.865776
|View full text |Cite
|
Sign up to set email alerts
|

Can’t Disconnect Even After-Hours: How Work Connectivity Behavior After-Hours Affects Employees’ Thriving at Work and Family

Abstract: As more organizations adopt telecommuting or working from home, the work-connected behavior of their employees during non-working hours increases, weakening the boundary between work and family. However, no study has clearly identified whether and how work connectivity behavior after-hours (WCBA) affects employees’ work and family status. Therefore, using role theory, we explored the mechanisms by which WCBA affects employees’ thriving at work and family through work–family enrichment and work–family conflict,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Based on job characteristics model, we explore the moderating effect of skill variety and job autonomy on the relationship between human–machine interaction and employee’s vitality, and the results support the point that job characteristics have an impact on employee’s psychology ( Hackman and Oldham, 1976 ; Grzywacz and Marks, 2000 ; Bell and Kozlowski, 2008 ). However, employee’s vitality is not only affected by job characteristics ( Spreitzer et al, 2010 ), but also has a relationship with one’s psychology ( Yang et al, 2022 ), so we introduce competence perception and study the triple-interactive effects of human–machine interaction, job characteristics, and competence perception on employee’s vitality. This study expands the research on the relationship between human–machine interaction and employee’s psychological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Based on job characteristics model, we explore the moderating effect of skill variety and job autonomy on the relationship between human–machine interaction and employee’s vitality, and the results support the point that job characteristics have an impact on employee’s psychology ( Hackman and Oldham, 1976 ; Grzywacz and Marks, 2000 ; Bell and Kozlowski, 2008 ). However, employee’s vitality is not only affected by job characteristics ( Spreitzer et al, 2010 ), but also has a relationship with one’s psychology ( Yang et al, 2022 ), so we introduce competence perception and study the triple-interactive effects of human–machine interaction, job characteristics, and competence perception on employee’s vitality. This study expands the research on the relationship between human–machine interaction and employee’s psychological behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we adopted the research methods used by other scholars, and the data collection was completed by using an online survey questionnaire through the online platform Credamo in China ( Gong et al, 2020 ; Yang et al, 2022 ). The questionnaire method is generally applied in management research, and this online format allows us to collect a sizable and trustworthy sample conveniently.…”
Section: Methodsmentioning
confidence: 99%
“…In another research among Italian workers (diverse occupations), only in the male subsample, there was a positive association between work-related after-hours ICT use and work–family/life enrichment, while in the female group, although positive, the relationship was non-significant ( Ghislieri et al, 2017 ). In a third study, among Chinese participants from diverse occupations, the relationships between after-hours work-related ICT use and work–family/life enrichment were also positive; however, there was what the authors called a “double-edged sword effect,” as work–family/life enrichment on its turn was positively related to thriving at work but also to work–family/life conflict ( Yang et al, 2022 ). As for the fifth study, also developed among Chinese workers, although no significant direct relationship was found between after-hours work-related ICT use and work–family/life enrichment, there was a positive mediating effect of work-based resource gain between those variables ( Wan et al, 2019 ).…”
Section: Characterization Of Studies and Qualitative Description Of R...mentioning
confidence: 99%
“…The great majority of studies found that work-related after-hours ICT use was positively related to work–family/life conflict, such as among Italian workers ( Ghislieri et al, 2017 ), Portuguese company service employees ( Carvalho et al, 2021 ), North American workers ( Fenner and Renn, 2010 ; Harris et al, 2011 , 2022 ; Richardson and Thompson, 2012 ; Chen and Karahanna, 2014 ; Wright et al, 2014 ; Yue, 2022 ), Canadian workers ( Schieman and Young, 2013 ), and Chinese workers ( Wan et al, 2019 ; Yang et al, 2022 ) particularly if the interruption is initiated by others compared to initiated by the worker ( Khalid et al, 2022 ). Tams et al (2020) , in a study among North American knowledge workers, showed that perceived work-related after-hours ICT interruption was positively related to work–family/life conflict; however, this effect may be attenuated by workers’ perceptions of control over work.…”
Section: Characterization Of Studies and Qualitative Description Of R...mentioning
confidence: 99%